From transplant to novel cellular therapies in multiple myeloma: European Myeloma Network guidelines and future perspectives - Gay, Francesca; Goldschmidt, Hartmut (Haematologica, 2018)
Survival of myeloma patients has greatly improved with the use of autologous stem cell transplantation and novel agents, such as proteasome inhibitors, immunomodulatory drugs and monoclonal antibodies. Compared to bortezomib- and lenalidomide-based regimens alone, the addition of high-dose melphalan followed by autologous transplantation significantly improves progression-free survival, although an overall survival benefit was not observed in all trials. Moreover, follow up of recent trials is still too short to show any difference in survival. In the light of these findings, novel agent-based induction followed by autologous transplantation is considered the standard upfront treatment for eligible patients (level of evidence: 1A). Post-transplant consolidation and maintenance treatment can further improve patient outcome (1A). The availability of several novel agents has led to the development of multiple combination regimens such as salvage treatment options. In this context, the role of salvage autologous transplantation and allotransplant has not been extensively evaluated. In the case of prolonged remission after upfront autologous transplantation, another autologous transplantation at relapse can be considered (2B). Patients who experience early relapse and/or have high-risk features have a poor prognosis and may be considered as candidates for clinical trials that, in young and fit patients, may also include an allograft in combination with novel agents (2B). Ongoing studies are evaluating the role of novel cellular therapies, such as inclusion of antibody-based triplets and quadruplets, and chimeric antigen receptor-T cells. Despite encouraging preliminary results, longer follow up and larger patient numbers are needed before the clinical use of these novel therapies can be widely recommended.
Gesehen am 12.09.2019